A directed co-assembly of herbal small molecules into carrier-free nanodrugs for enhanced synergistic antitumor efficacy. Issue 4 (4th January 2021) - Wang, Jiacheng; Qiao, Wenshu; Li, Xu; Zhao, Haitian; Zhang, Hua; Dong, Aijun; Yang, Xin
Abstract : The supramolecular co-assembly properties of natural small molecules were revealed and carrier-free nano-drugs without structural modification were constructed. Abstract : Carrier-free nanomedicines without structural modification are attractive for the development of natural small molecules (NSMs) and biomedical applications. Moreover, the combination of NSMs is expected to obtain nanomedicines with high efficacy and low side effects due to their inherent pharmacological activities and health benefits. However, poor water solubility and low bioavailability of NSMs limit their wider biomedical and clinical applications. In this study, we revealed the co-assembly properties of pentacyclic triterpenoids and constructed a series of carrier-free nanodrugs, which are co-assembled nanoparticles (NPs) formed by the combination of two NSMs via a supramolecular assembly strategy. Experimental work and simulation studies were combined to reveal the co-assembly mechanism of non-covalent interactions between NSMs. Not only do co-assembled NPs have rapid cellular uptake ability and passive targeting tumor ability based on the EPR effect, but also their constituent units could arrest the cell cycle at different stages of tumor cells and induce apoptosis, showing synergistic anti-tumor effects (CI < 0.7). Compared with self-assembled NPs and positive control, co-assembled NPs show the strongest therapeutic effect in vivo . Importantly, the co-assembled NPs highlight the unique advantages of NSMs in terms of biosafety and health benefits, and systemic toxicity and histological examination confirm that co-assembled NPs have reliable biosafety, and no side effects and nano toxicity risks were observed.